The Influence of Hypertension and High-Density Lipoprotein on the Diabetic Nephropathy Patients - Marniati, Marniati; Husna, Arafah; Maifizar, Afriani; Putri, Enda Silvia (Universitas Muhammadiyah Yogyakarta, 2020)
Diabetes complication of kidney failure begins with poor control of High-Density Lipoprotein (HDL) levels causing constriction of efferent arterioles affecting microalbuminuria, which triggers hypertension due to damage to blood vessels, with scarring in the filtration system of the central part of the kidneys. The Objective of the research was to analyze the influence of hypertension and HDL on the diabetic nephropathy patients. The study was an observational analytic study with a case-control design. The research sample consisted of 32 sample cases of patients with type II DM complications of kidney failure, and 32 control samples were DM type II patients without complications of kidney failure in dr. Pirngadi Hospital, Medan with accidental sampling technique. Data were generated by using questionnaires and medical records and analyzed by using the chi-square test, independent t-test, Mann-Whitney, and multivariate logistic regression to identify the effect of HDL and hypertension with DM type II complications of kidney failure. The Result of multivariate analysis showed hypertension OR; 17.845, and HDL OR; 7.049. The Conclusion showed that the most dominant factor that influenced the incidence of kidney failure complications in DM type II patients was hypertension at the Population Attributable Risk of 91%.